On the formation of defects induced by air trapping during cold pressing of PTFE powder. (15th January 2016) - Gamboni, Otávio C.; Riul, Cassius; Billardon, René; Bose Filho, Waldek W.; Schmitt, Nicolas; Canto, Rodrigo B.
Abstract: The manufacturing of polytetrafluoroethylene products is usually carried out by cold isostatic and/or uniaxial pressing of the powdered polymer, followed by sintering of the "green" parts. During pressing, the air initially present in the loose powder leads to the formation of defects in the material, but the mechanisms involved are not entirely understood. The aim of this study was to better understand the role played by the entrapped air during the cold pressing of polytetrafluoroethylene powder. Observation of the microstructure and determination of some mechanical properties of green and sintered samples, manufactured with different quantities of entrapped air by the cold isostatic pressing process, were carried out. The analysis indicated that defects are formed when the entrapped air pressure in the pressed part leads to internal stresses exceeding the intergranular cohesion resistance of the green part. These defects remain in the microstructure even after sintering, considerably reducing the mechanical strength. Graphical abstract: Highlights: The entrapped air plays a major role in the defects formation in the sintered PTFE. An analytical model was used to predict the formation of defects on green material. Mechanical properties of the PTFE pressed with air extraction was greatly enhanced. Presence of warts on the fracture surface reveals processing defects in components.